THEORETICAL BASIS OF INVESTMENT ACTIVITY - Levandivskyi , O.T. (The actual problems of regional economy development, 2016)
In the article, going of economists isinvestigational near determination of primary objective ofinvestment activity. Three basic approaches are shown ingenesis of this problem. It is marked that modern investmentactivity closely constrained and concerted with economicpolitics. Also, two main loops of investment process areexamined. Basic conceptions that presently is actively used in aninvestment management as a methodical tool of decision ofthe applied tasks are distinguished. It is shown, whatelements are included in the structure of mechanism ofinvestment management. It is marked that the system of investment management willrealize the primary objective and basic tasks by realization ofcertain functions. These functions are divided into two basicgroups conditioned by complex maintenance of consideredcontrol system by investment activity. JEL: E 62